Calcium Reduction Using Variations of Thickness and Retention Time of Cocoa Shell Activated Carbon - Muadifah, Afidatul; Santoso, Arif; Ngibad, Khoirul; Martha, Rahma Diyan; Kholifah, Siti Nurriyatul (Chempublish Journal, 2023)
High levels of hardness can lead to increased cases of kidney stones. Hardness levels can be reduced by using activated carbon from the cocoa rind as an adsorbent. The purpose of this research was to determine the variation of activated carbon thickness and optimum retention time in reducing the calcium content of dug well water, to determine the percent decrease in calcium ion levels at the optimum variation, and to determine the significance of the difference in the decreased in calcium levels between the treatment groups. The research method used the principle of adsorption of activated carbon from cocoa shells to calcium ions, which are activated by KOH. There were ten treatment samples with different variations of activated carbon thickness and retention time. The results showed that the thickness of activated carbon of 60 cm with a retention time of 50 minutes had the optimum ability to reduce the calcium content of dug well water. The percentage decrease in calcium levels reached 89,041 % with a decreased concentration of 234 ppm. The result of the statistical test showed a significance value of 0,05. The conclusion of the research is that activated carbon of cocoa shells can reduce calcium levels to the levels of soft water hardness, with variations in activated carbon thickness and retention time having a significant effect.